Uma análise de síntese em escala nacional de mudanças climáticas nas áreas protegidas do Brasil - Paula, Larissa Carpigiani de [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The environmental impacts caused by climate change will hit, without exceptions, the whole globe, including protected areas. The National System of Conservation Units (SNUC in the acronym in Portuguese) predicts the creation and management of Conservation Units (UCs) in Brazil. However, this law does not predict the management and minimization of the impacts driven by climatic changes inside UCs. As such, this study aimed at updating and improving a database that relates climate change projections in the Brazilian protected areas (APs, including indigenous lands), considering as well the biome in which it is found. To do that the study employed maps with information on the geographical boundaries of the APs, of the Brazilian biomes and data on temperature and precipitation for 2050 under four radiative forcing scenarios used in Intergovernmental Panel on Climate Changes (IPCC) Fitfth Assessment Report. Results were compared and analysed through the elaboration of a ranking showing the APs with higher risk of severe climatic change (higher temperature increase and changes in precipitation). Major results show that APs located in Amazonia, Cerrado and Pantanal biomes are among the ones to be most affected, with highest temperature increase (2.5ºC and >3ºC) and moderate reduction of precipitation (-25 to -100mm/y). Nevertheless, APs within the Atlantic Forest and the Marine-Coastal zone also show moderate increase in temperature and severe changes in precipitation. For an extreme threshold temperature of +3ºC there has been the predominance of APs that count with the presence of traditional populations, in Amazonia and Cerrado. Besides serving as a starting point for studies on how climate change will ecologically and socially affect these APs, our results shall be useful for the elaboration of public policies aiming at the adaptation of APs to climatic change in Brazil

Os impactos ambientais provenientes das mudanças climáticas atingirão, sem exceções, todo o globo, inclusive áreas protegidas (APs). O Sistema Nacional de Unidades de Conservação (SNUC) institui a criação e manejo de Unidades de Conservação (UCs) no Brasil. Porém, este instrumento legal de conservação não é planejado para gerir e minimizar os impactos dentro de UCs, gerados pelas alterações climáticas. Sendo assim, este trabalho visou atualizar e aperfeiçoar um banco de dados que relaciona projeções de mudanças climáticas nas áreas protegidas brasileiras, inserindo nele também informações relativas aos biomas brasileiros em que elas se encontram. Para este trabalho, foram sobrepostos mapas com informações referentes aos limites de áreas protegidas, dos biomas brasileiros e dados de temperatura e precipitação para 2050 sob quatro cenários de forçantes radioativas utilizados no quinto relatório do Painel Intergovernamental de Mudanças Climáticas (IPCC). Os diferentes resultados foram comparados e analisados por meio da construção de um ranking das áreas protegidas em maior risco de mudanças climáticas severas (maiores aumentos de temperatura e mudanças de precipitação). Como principais resultados, obteve-se que as APs pertencentes aos biomas Amazônia, Cerrado e Pantanal, entre as mais afetadas, com os maiores aumentos de temperatura (2,5ºC e >3ºC) e redução moderada de precipitação (-25 e -100mm/a). Destaca-se também as APs nos biomas Mata Atlântica e Marinho Costeiro, que embora apresentem aumentos moderados de temperatura, sofrerão, de acordo com as projeções, mudanças severas de precipitação. Para APs com aumento extremo de temperatura maior que 3ºC, observou-se predominância de APs que contam com a presença de populações tradicionais, na Amazônia e Cerrado. Além de servir como um ponto de partida para estudos sobre como as mudanças climáticas...
Keywords: Climatologia; Mudanças climáticas; Áreas protegidas; Áreas de conservação de recursos naturais; Unidades de conservação; Ecossistemas; Impacto ambiental; Brasil